Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. Role of School Administration Towards Caring Gifted Students in Model Secondary Schools in Aden Governorate from the Teachers’ Point of View Co-Prof. Fahad Ali Abdullah , Dr. Dhahiba Saeed Saleh 2. The role of the national case management system in achieving protection for vulnerable children in the Republic of Yemen 2024 AD-1446AH Mr. Abdulghani Abdulaziz Abdu Naji Al-Humaidi 3. Analysis of the Educational Policy Document in the Kingdom of Saudi Arabia in Light of Global Future Trends in Education Ms. Wardah Ali Al-Rzouq, Ms. Hamida Ahmed Al-Zakari, Prof. Fatima Abdullah Al-Bishr 4. The impact of using generative artificial intelligence applications on developing digital educational content creation skills and the attitudes of female trainers and trainees at the Girls’ Technical College towards them Ms. Imtinan Mohammed Alzughaibi, Co-Prof. Leena Ahmed Alfarani 5. Educational signification extracted from the verses of mother in the holy Quran and their applications in the family Ms. Nourah Dakhel Al-Nefaie 6. The Relationship between Intelligence Quotient with Variables among Kindergarten Children in Khartoum State Dr. Nada Izzeldeen Jafar 7. Suicide ideation among Sudanese adults cross in Khartoum state Sudan Dr. Radwa Mohamad Ibrahim, Dr. Fath-Alrhman Omer Alsharif, Dr. Nadir Elzain Omara